2019
DOI: 10.3390/math7030246
|View full text |Cite
|
Sign up to set email alerts
|

A Theoretical Rigid Body Model of Vibrating Screen for Spring Failure Diagnosis

Abstract: Springs are critical components in mining vibrating screen elastic supports. However, long-term alternating loads are likely to lead to spring failures, likely resulting in structural damages to the vibrating screen and resulting in a lower separation efficiency. Proper dynamic models provide a basis for spring failure diagnosis. In this paper, a six-degree-of-freedom theoretical rigid body model of a mining vibrating screen is proposed, and a dynamic equation is established in order to explore the dynamic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Six kinds of spring failure were selected for simulations, and the results indicated that the spring failures led to an amplitude change of the four elastic support points in the x, y, and z directions, where the changes depended on certain spring failures. The conclusions provided a theoretical basis for further study and experimentation on spring failure diagnosis for mining vibrating screens [29].…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…Six kinds of spring failure were selected for simulations, and the results indicated that the spring failures led to an amplitude change of the four elastic support points in the x, y, and z directions, where the changes depended on certain spring failures. The conclusions provided a theoretical basis for further study and experimentation on spring failure diagnosis for mining vibrating screens [29].…”
Section: Introductionmentioning
confidence: 90%
“…Furthermore, several kinds of spring failure were selected, as shown in Table 2. In [29], the stiffness variation coefficient (SVC) ∆k i and the amplitude variation coefficient (AVC) ∆λ id are proposed for normalization of the stiffness and amplitude change, namely,…”
Section: Spring Failure Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The amplitude of the vibrating screen will increase significantly due to resonance, and it will also affect service life of the equipment. The vibrating screen usually uses rubber or metal springs as support, which is also a vibration isolation device with the installation foundation [3,4]. Even though with simple structure and low price, the common isolators cannot adjust the stiffness and make corresponding changes according to the actual working conditions, which leads to their poor vibration isolation efficiency and large noise.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, we can find spatial models of vibrating conveyors. However, these models are simplified to the dynamics of the movement of the trough in which the vibrator action is replaced by a concentrated axial force [12]. Such models cannot reflect the couplings between vibrators and the body [6] and thus the process of self-synchronisation of the vibrators, which is extremely important for the correct operation of the machine [9][10] [8][1] [22] [19] [21] cannot be captured.…”
Section: Introductionmentioning
confidence: 99%